UPAYA PEMERINTAH KABUPATEN BINTAN DALAM MENINGKATKAN KUNJUNGAN WISATAWAN SINGAPURA TAHUN 2016-2018 - Sinta Asmara; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research aims to explain the policies issued by the central government and regional governments in developing the tourism sector of Bintan Regency and the efforts made to improve the visit of Singaporean tourists in Bintan Regency.This research uses the perspective of globalization, the level of analysis of the state, the theory of international cooperation and the concept of international tourism. The method used is a descriptive qualitative research method. This analysis is based on data obtained from literature studies and field studies, interviews with informants who are considered capable of providing information.The results of the research in this paper about the Singaporean tourist arrivals increased from 2016-2018. The increase in Singapore tourist benefits is influenced by mutually sustainable central and local government policies. The efforts of the Bintan Regency government to increase Singapore tourist arrivals in 2016-2018 are a collaboration between the Bintan Regency and PT. Bintan Resort Cakarawala, organizes international events, promotes Bintan tourism in Singapore, and improves tourism support facilities. Keywords: Bintan Regency, Singapore, PT. Bintan Resort Cakrawala (BRC), International Tourism, Globalization.